From Marx to Heidegger: Oscar del Barco and the crisis of Marxism. (7th December 2021) - Bosteels, Bruno
Abstract : This article traces the path from Marx to Heidegger along which the Argentine philosopher Oscar del Barco responded to the crisis of Marxism. Interrogating Heidegger's own suggestion of a 'fruitful dialogue' with Marx's thinking of history and alienation, Del Barco gradually moved to a critique of Marxism as being part and parcel of the twice millenarian tradition of Western metaphysics. If, in an earlier collection such as El otro Marx, he still believed in the possibility of retrieving the 'other side' of capitalist reason in the margins of Marx's texts, starting in the collection El abandono de las palabras this hope gives way to a mystical or messianic expectation to welcome the sheer 'there is' of being through an attitude of non-doing that would be neither nihilist nor conformist. In this sense Del Barco's itinerary can be considered paradigmatic of the way in which a whole school of radical theory and philosophy responded to the crisis of Marxism as part of a much vaster, epochal or civilisational crisis of reason and technology in the West.